Decentralization, happiness and the perception of institutions - Luis Diaz-Serrano; Andrés Rodríguez-Pose (Institute for the Study of Labor (IZA), 2011)
This paper analyses whether the different powers and resources at the disposal of local and regional governments across Europe deliver greater satisfaction with political institutions and lead to greater personal happiness. The analysis uses microdata from the four available waves of the European social survey (2002, 2004, 2006 and 2008), including more than 160,000 observations of individuals living in 29 European countries. Our results reveal that political and fiscal decentralization have a positive and significant effect on individuals' overall happiness. Fiscal decentralization also exerts a significant effect on the level of satisfaction with political and economic institutions and with the education and health systems, whereas the effect of political decentralization on these variables is more limited. The results show that citizens seem to be happier with the actual capacity of their local governments to deliver than with the general principle that they can have a say on their daily politics and policies.
urn:nbn:de:101:1-201104193344
Keywords: H11; H77; 330; happiness; well-being; satisfaction; fiscal and political decentralization; Europe; Dezentralisierung; Finanzföderalismus; Wahrnehmung; Zufriedenheit; Partizipation; Europa